Analisis Pengaruh Frekuensi Osilasi Pegas Terhadap Tegangan Listrik yang Dihasilkan Alat Peredam Kejut Regeneratif Elektromagnetik Skala Laboratorium - Sidik Susilo; Yusvardi Yusuf; Syarif Abdullah; Muhammad Reza Ghifari; Baskoro Adi Hermawan (Universitas Muhammadiyah Surabaya, 2022)
Abstract— EMRSA is a tool that can generate electrical energy by utilizing vibration energy that is wasted in a vehicle. Vibration energy includes energy that is wasted on vehicles and is still very rarely used. Therefore, in this study, an experiment was carried out to convert vibration energy into electrical energy. The purpose of this study was to determine the effect of the frequency of spring oscillations on the electric voltage produced by a laboratory-scale regenerative shock absorber. The research was carried out by providing variations in the load on the spring so that a different frequency was obtained in each experiment. The results of the experiment show that the frequency of the spring oscillation is directly proportional to the result of the electric voltage generated. The higher the frequency given, the greater the resultant voltage generated. From the experiments that have been carried out, the results of the electrical voltage of 0.537 volts are obtained at a frequency of 3.37 Hz with a number of copper coils of 500 turns and a copper diameter of 0.1 mm.